A case study: factors contributing fluctuation in world oil price / Nuraisha Mohd.Fadzil - Mohd.Fadzil, Nuraisha (Faculty of Business and Management, 2011)
This study will reveal the factors contributing fluctuation in world oil price. The factors are the main highlight in finding the reason behind fluctuation in world oil price since most of the time we are shocked by the news of oil, which day by day the price is crazily towering as high as KLCC. Thus, this study will find out how the instability of world oil price may affect the performance of PETRONAS as an oil and gas business entity. First and foremost, the researcher will analyze the world oil price data to deep down the fluctuation trend and relate to the factors that may contribute to high oil price. After notified the factors, again the researcher will find the gap identification to analyze the connection of the factors and the performance of PETRONAS. To analyze the performance of PETRONAS, the researcher using a validate data such as the financial report, the sales revenue data, the profit before tax data, the net profit data, and the cost and the crude oil price data. These data can be retrieved through PETRONAS Annual Report. By processing the data, thus at the end of the study will come out with a result.